Expectations and demands in online teaching : practical experiences - Gudea, Sorin Felician Walter (Hershey : Information Science Pub., 2008)
"This book offers a better understanding of how teachers experience the online environment by exploring various dimensions of online teaching"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Teaching -- Computer network resources; Computer-assisted instruction; Distance education; Internet in education